As mazelas do CS: GO feminino no Brasil - Oliveira, Leonardo Biazzi Garcia de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
As mazelas do CS:GO feminino no Brasil is a multimedia reporting, that seeks to explain the work conditions of women that play Counter Strike: Global Offensive professionally, to approach the current scenario of semi profissionalism and give voice to these players, so they talk about structural problems like male chauvinism or harassment. CS:GO is a game that has become an electronic sport, which has several international championships, alongside television coverage and many fans. In Brazil, the scene has not evolved as much as in the United States or Europe, especially when it comes to women playing CS: GO. They do not play as much as man, have difficulties in arranging teams that offer good working conditions, they compete a few championships compared to men and have to deal with male chauvinism rooted in game culture. I used the Medium platform because it delivers a simple and effective design, besides being free

As mazelas do CS:GO feminino no Brasil é uma reportagem multimídia, que procura esclarecer as condições de trabalho que as jogadoras enfrentam, abordar o cenário atual de semi profissionalismo da categoria e dar voz à essas jogadoras, para que elas falem de problemas estruturais como o machismo ou assédio. Counter-Strike: Global Offensive é um jogo que tornou-se um esporte eletrônico, que conta com diversos campeonatos mundiais, com cobertura televisiva e uma legião de fãs. No Brasil, a cena ainda não evoluiu tanto quanto nos Estados Unidos e no continente europeu, ainda mais quando tratamos sobre as mulheres que jogam CS:GO. Elas estão em menor número, possuem dificuldades para arrumar times que ofereçam boas condições de trabalho, disputam poucos campeonatos comparados com os homens e precisam lidar com o machismo enraizado da indústria dos games. Utilizei a plataforma Medium, pois ela entrega um design simples e efetivo, além de ser grátis
Keywords: Jornalismo; Mulheres; Jogos eletronicos; Games